Implementing a Collaboration Platform : Making Behavior Change Part of the Plan - Devine, Jacqueline; Silverman, Sheryl (World Bank, Washington, DC, 2012)
For two global programs a rural sanitation project and a hand-washing project with the goals of scaling up access to sanitation and increasing hygiene behaviors how can lessons be shared easily and efficiently with a global team across six countries, including headquarters-based staff? That is what the Water and Sanitation Program (WSP) sought to do in 2008 by creating a virtual collaborative workspace, www.learningtoscaleup.org. This smart lesson documents the challenges of trying to create a cultural shift from communicating primarily via e-mail and phone calls to using a virtual platform. Although the platform is no longer used, the lessons learned from the experience might help inform other teams seeking to create a platform.